2016
DOI: 10.1016/j.bjan.2016.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Análise da aplicação de pressão cricoide: residentes em anestesiologia vs. enfermeiros assistentes de anestesia

Abstract: The anaesthetic trainee doctors were better than the nursing anaesthetic assistants in cricoid cartilage identification but both groups were equally poor in their knowledge and application of cricoid pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Even though the efficacy of cricoid pressure in preventing pulmonary aspiration had controversial results, 2,25 it is better to at least try to prevent aspiration with cricoid pressure in a low-income country to prevent serious postoperative sequelae and it may be of huge importance for a low-income setting where intensive care beds are very scarce.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though the efficacy of cricoid pressure in preventing pulmonary aspiration had controversial results, 2,25 it is better to at least try to prevent aspiration with cricoid pressure in a low-income country to prevent serious postoperative sequelae and it may be of huge importance for a low-income setting where intensive care beds are very scarce.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our finding some studies reported that health care professionals had poor knowledge in identifying the cricoid cartilage, the amount of cricoid pressure force required, and the correct application of cricoid pressure. 2,34,35 Most of our study participants had poor knowledge and skill regarding when cricoid pressure is released. Similarly, research conducted by Krishnan et al health professionals had inadequate knowledge when cricoid pressure is released.…”
Section: Dovepressmentioning
confidence: 97%
See 1 more Smart Citation